Teknik pemodelan untuk mengurangi perilaku mengganggu pada anak - Noor Latifah Andina (Procedia : Studi Kasus dan Intervensi Psikologi, 2021)
The client is a 7 year old boy who complains of disturbing his friends and relatives at home. The results of the assessment through interviews, observations, psychological tests (CPM) and the Destructive Behavior Disorder Rating Scale (DBD) found that clients have problems with disruptive behavior, with a background problem in learning the wrong way from their environment. The goal of the intervention is to reduce the client’s disruptive behavior. The intervention given is Symbolic Modeling Technique using video and role play. The results of the intervention show a decrease in the client’s disruptive behavior and are used as guidelines or new, more positive patterns.